2010
DOI: 10.1155/2010/349248
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Relationship between Changes in Meteorological Conditions and the Variation in Summer Ozone Levels over the Central Kanto Area

Abstract: An increasing trend in ground-level ozone () concentrations has recently been recognized in Japan, although concentrations of ozone precursors, nitrogen oxides (NOx), volatile organic compounds (VOCs) and nonmethane hydrocarbons (NMHCs) have decreased. In this paper, the relationship between meteorological factors (temperature and wind speed) and ground-level ozone concentrations in the summer over the central Kanto area of Japan was examined using both statistical analyses and numerical models. The Fifth-Gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 43 publications
0
23
0
Order By: Relevance
“…Variations in meteorological parameters influence the efficiency of photochemical production and loss of surface O 3 [38,80]. Solar radiation and enhanced air temperatures play catalytic roles in chemical reactions, leading to surface O 3 formation [81].…”
Section: Impact Of Meteorological Parameters On O 3 and Nomentioning
confidence: 99%
See 1 more Smart Citation
“…Variations in meteorological parameters influence the efficiency of photochemical production and loss of surface O 3 [38,80]. Solar radiation and enhanced air temperatures play catalytic roles in chemical reactions, leading to surface O 3 formation [81].…”
Section: Impact Of Meteorological Parameters On O 3 and Nomentioning
confidence: 99%
“…Changes in local weather conditions can greatly affect the surface O 3 concentrations [29][30][31][32]. Therefore, analyzing the long-term variations in weather change that occur at a particular location is very useful for understanding the concentration of surface O 3 concentrations [33][34][35][36][37][38]. Many studies [39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55] on the variations of O 3 and its precursor gases revealed that higher surface O 3 concentrations were observed in summer/autumn seasons and lower concentrations were observed during monsoon season.…”
Section: Introductionmentioning
confidence: 99%
“…The variables selected in this study are based on previous study of O 3 concentrations level (Table 1) Meteorological variable: Khiem et al (2010) found that the low wind speed which associated with the other meteorological conditions has a high ability to contribute O 3 concentrations. Urban area has very little difference of O 3 concentrations level with rural area during high wind speeds (Husar and Renard, 1997).…”
Section: Variable Selectionmentioning
confidence: 99%
“…The impacts of UHI include elevated emissions of air pollutants and greenhouse gases, such as sulfur dioxide (SO 2 ), nitrogen oxide (NO x ), volatile organic compounds (VOC s ), particulate matter, carbon monoxide (CO), carbon dioxide (CO 2 ), and mercury (Hg). In addition to energy‐related elevated emissions, high temperatures can directly increase the rate of ground‐level formation of ozone [ Kheim et al, ; Ooka et al, ], which is formed when NO x and VOC s react in the presence of sunlight and hot weather. Further oxidation of NO 2 and SO 2 by ozone and hydroxyl radicals form HNO 3 and H 2 SO 4 , which react with NH 3 to form hygroscopic aerosols such as NH 4 NO 3 , NH 4 HSO 4 , and (NH 4 ) 2 SO 4 .…”
Section: Introductionmentioning
confidence: 99%